A CONCISE PICTURE OF HERNIA - ROY, ATHIRA; RAVI, KRISHNA; T REJI, REEJA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
A hernia is a disease wherein organs or tissues, like the bowel, bulge through the abdominal wall. The etiological, as well as precipitating factors for hernia include abdominal pressure, pre-existing weakness of abdominal muscles, gender, obesity, age, diet, lack of regular exercise, and smoking. Swelling, stiffness, and discomfort seem to be the most prevalent hernia symptoms, particularly while straining, moving, or bending down. Open and laparoscopic techniques are mainly used for hernia repair, both use mesh to counterbalance the abdominal wall flaws and provide a tension-free restoration.